Local participation in cultural landscape maintenance: Lessons from Sweden - Stenseke, Marie (Land use policy, 2009)
Local participation has evolved as a strategy in the conservation and maintenance of biological and cultural values in cultural landscapes. The meaning(s) of the concept, however, are fuzzy, and conditions for fruitful implementation have only been investigated to a limited extent. In this article, a couple of Swedish cases serve as points of departure for a better understanding of the prerequisites and critical aspects as regards an increased local involvement in landscape management. A review of research on community participation reveals some essential aspects; power relations, participants, the institutional framework, organisation, communication, knowledge building, monitoring and contextual factors. These aspects have formed the structure for the analysis of two cases within which local involvement is considered successful; Southern Öland, where community involvement in seminatural grassland management has been experienced in LIFE-projects and in the process of becoming a UNESCO World heritage site, and Mälarhagar, an integrated restoration and beef production project carried out in close collaboration with farmers. The results are discussed in terms of successful ingredients, counterproductive aspects and operational difficulties. The findings show that trust, communication and local influence are vital ingredients in a participatory approach. Communication and co-management are pointed out as central areas of competence for executives working with landscape management and planning. There are, however, collisions between directives concerning nature conservation and directives concerning public participation. For successful local involvement, the subject for collaboration has to be broadly defined. Furthermore, the strong emphasis on collaboration in participatory approaches demands that democratic aspects have to be considered.